Pengaruh Brand Identity dan Brand Image terhadap Purchase Decision dengan Brand Trust sebagai Variabel Intervening: (Studi pada Konsumen Fiesta Chicken Nugget di Kota Tangerang) - Nabila Tria Amanda; Lutfi Lutfi; Diqbal Satyanegara (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study analyzes the relationship between Brand Identity (X1) and Brand Image (X2) that influence Purchase Decision (Y), while considering Brand Trust (Z) which functions as an intervening variable among buyers of Fiesta Chicken Nugget products in the Tangerang City area. Consumer decisions to purchase Fiesta Chicken Nugget products form the foundation of this research, where such decisions are associated with the brand identity and image embedded in the product. The research targeted a population of Fiesta Chicken Nugget product buyers residing in the Tangerang City area. Data collection involved 140 respondents selected using a combination of purposive sampling and convenience sampling methods. The data testing process utilized Structural Equation Modeling (SEM) techniques with SmartPLS 4.0.9.9 software as the analytical tool. The study findings revealed seven main results regarding the relationships between variables: First, it was proven that brand identity produces a significant positive impact on purchase decision. Second, brand image demonstrates a substantial positive effect on purchase decision. Third, brand identity is confirmed to exert a substantial positive influence on brand trust. Fourth, brand trust receives significant positive influence from brand image. Fifth, purchase decision is convincingly positively influenced by brand trust. Sixth, the role of brand trust as an intervening variable is confirmed between brand identity and purchase decision. Seventh, brand trust successfully demonstrates its function as a mediator connecting the influence of brand image on purchase decision.